2018
DOI: 10.1111/cid.12626
|View full text |Cite
|
Sign up to set email alerts
|

The effect of single tooth implant restorations on the survival, morbidity, pulpal, and periapical health of adjacent teeth: A chart review

Abstract: The incidence for restorative retreatment was significantly higher on teeth adjacent to implant restorations as compared to the contralateral controls. There were no significant differences in the survival, morbidity, pulpal, or periapical health of teeth adjacent to single tooth implants compared to those adjacent to the contralateral natural tooth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 16 publications
(30 reference statements)
1
13
2
Order By: Relevance
“…A case series analysis revealed that the majority of the adjacent teeth with VRFs were premolar or mandibular molar teeth and that all fractured teeth were restored with a crown and had a post present [24]. Duqum et al [26] demonstrated that the requirement for restorative retreatment was significantly higher for teeth adjacent to implant restorations than for the contralateral controls. Similarly, the results of a retrospective study conducted by Yoshino et al [27] revealed that the percentage of the loss of teeth adjacent to implant-supported restorations was higher than that of other posterior teeth.…”
Section: Introductionmentioning
confidence: 99%
“…A case series analysis revealed that the majority of the adjacent teeth with VRFs were premolar or mandibular molar teeth and that all fractured teeth were restored with a crown and had a post present [24]. Duqum et al [26] demonstrated that the requirement for restorative retreatment was significantly higher for teeth adjacent to implant restorations than for the contralateral controls. Similarly, the results of a retrospective study conducted by Yoshino et al [27] revealed that the percentage of the loss of teeth adjacent to implant-supported restorations was higher than that of other posterior teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the previously reported higher prevalence of decay in teeth adjacent to implants, it is expected that a higher prevalence of endodontic lesions, root canal fillings and restorations is these teeth, which has been partially confirmed by the present results, as higher odds of previous root canal fillings and coronal restoration were found when the tooth is adjacent to an implant-supported crown. Recent studies in teeth adjacent to implantsupported crowns observed an increased incidence of 12.4% of restorations over a 1-year period (Duqum et al, 2018), whilst the caries prevalence ranged between 7.4% and 40.0% depending on the interproximal width (Smith et al, 2020). Although comparisons with the result of the present study are difficult due to the different study designs (radiographs × CBCT) and outcomes assessed, both previous studies appear to support some deleterious effect on the teeth adjacent to implant-supported crowns in line with the present study (Tables 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…The few published studies have reported inconsistent results on the status of teeth adjacent to implants (Duqum et al, 2018;Krennmair et al, 2003;Smith et al, 2020); however, there is a consensus that the loss of proximal contacts is an issue that may lead to a deleterious effect on these teeth. These studies have documented the incidence of caries and periapical lesions on adjacent teeth using follow-up clinical records based on periapical films or digital radiographs, which display a well-known lower sensitivity when compared to other imaging modalities, such as the cone-beam computed tomography (CBCT).…”
Section: Introductionmentioning
confidence: 99%
“…Upkeep of the pulpal and periapical wellbeing of neighboring teeth is of imperative significance to forestall further treatment needs of patients getting dental and implant treatment. While, there has been broad research on implants and their restoration, there has been constrained investigation of their impacts on neighboring teeth (5) .…”
Section: Discussionmentioning
confidence: 99%